2016
DOI: 10.21182/jmisst.2016.00052
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Lumbar Foraminoplasty for Resection of Synovial Cyst

Abstract: Synovial cyst is an extradural mass that compresses nerve root or thecal sac. Surgical excision with partial hemilaminectomy and medial facetectomy is commonly used for synovial cyst. Remarkable advancements in endoscopic spinal surgery have led to successful outcomes comparable to conventional open surgery. Here we introduce percutaneous endoscopic lumbar foraminoplasty for resecting synovial cyst as a minimal invasive technique. A 59-year-old woman presented with radicular pain at left L5 dermatome. Magnetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
(26 reference statements)
0
2
0
3
Order By: Relevance
“…Many articles have reported that patients experience a great amount of pain during foraminoplasty, so most surgeons use anesthetics (10–20 ml) on the SAP surface [10, 12, 13, 3437]. We have not experienced this problem in our practice, perhaps because we routinely coagulate the soft tissue on the SAP's ventral surface before conducting the Kiss-Hug maneuver.…”
Section: Discussionmentioning
confidence: 99%
“…Many articles have reported that patients experience a great amount of pain during foraminoplasty, so most surgeons use anesthetics (10–20 ml) on the SAP surface [10, 12, 13, 3437]. We have not experienced this problem in our practice, perhaps because we routinely coagulate the soft tissue on the SAP's ventral surface before conducting the Kiss-Hug maneuver.…”
Section: Discussionmentioning
confidence: 99%
“…This is done after adequate decompression surgery or solely relies on indirect decompression with restoration of disc height without decompression. Long-term results with fusion surgery are awaited though it looks highly promising in the initial reports 66,[123][124][125][126][127][128][129] . When done under general anaesthesia intraoperative neuromonitoring is mandatory 123,126,128) .…”
Section: ) Transforaminal Endoscopic Lumbar Foraminotomy (Telf)mentioning
confidence: 99%
“…Также подтвержден факт взаимосвязи между развитием параартикулярной кисты и МР-симптомами остеоартрита [23]. Консервативное лечение во многих описанных случаях оказывается недостаточно эффективным [3,4,5,8,9], что не противоречит нашим наблюдениям.…”
Section: клинические исследованияunclassified
“…В последние годы появились работы, освещающие целесообразность использования перкутанных видеоэндоскопических технологий в лечении ЭК поясничного отдела позвоночника. Однако большинство из них представляют собой небольшие серии наблюдений с непродолжительным катамнезом [8,10,13,17,19]. Доля рецидивов, потребовавших повторной операции, минимальна -2,1%.…”
unclassified
See 1 more Smart Citation